2005
DOI: 10.1080/02699050410001720095
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mild closed head injury on involuntary saccadic adaptation: Evidence for the preservation of implicit motor learning

Abstract: No differences in adaptation were found between the CHI group and the controls (F(1, 29) = 0.51, p = 0.48). This finding indicates that mild CHI does not impair implicit reflexive saccade adaptation and suggests that cerebellar function and functions of deeper brain structures such as the thalamus, superior colliculus and the basal ganglia may be largely preserved following mild CHI. The current results support the notion that the profile of oculomotor function after mild CHI reflects a centripetal gradient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…planning and execution of saccadic eye movements) and tracking (e.g. smooth pursuit) of visual targets (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). For example, in a recent study using a cued saccadic RT paradigm to compare participants with remote mild TBI to uninjured controls, we found evidence for persistent saccadic impairment among those with multiple previous injuries and/or chronic symptoms, whereas asymptomatic participants with a single mild TBI performed similarly to controls (35).…”
Section: Introductionmentioning
confidence: 79%
“…planning and execution of saccadic eye movements) and tracking (e.g. smooth pursuit) of visual targets (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). For example, in a recent study using a cued saccadic RT paradigm to compare participants with remote mild TBI to uninjured controls, we found evidence for persistent saccadic impairment among those with multiple previous injuries and/or chronic symptoms, whereas asymptomatic participants with a single mild TBI performed similarly to controls (35).…”
Section: Introductionmentioning
confidence: 79%
“…Consequently, it is an intriguing finding of this study that motor measures assessing the function of 'deeper' brain structures, the functional integrity of which is a factor in deciding outcome, are indeed associated with level of recovery. In all motor-based models, these 'subconscious' motor functions featured alongside motor functions that are more influenced by aspects of volitional control (e.g., directional errors, latencies, motor accuracy), primarily mediated by frontal, prefrontal, parietal and temporal cortical motor areas [46,47,68,76]. Due to the complex functional neuroanatomy employed for eye and arm motor processing, motor testing is able to simultaneously sample cortical and subcortical brain function.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that mild CHI impairs the complex cerebral networks for eye and arm motor control at 1 week post-injury, causing deficits in volitional saccades, oculomotor smooth pursuit, and upper-limb visuomotor function [44][45][46][47]. These motor deficits occur independently of neuropsychological impairment after mild CHI [46].…”
Section: Introductionmentioning
confidence: 92%
“…This finding is consistent with the findings reported by Heitger and coworkers. 56 Currently, there are no objective markers to predict which mTBI sufferers will transform to chronic, complicated cases in the mTBI spectrum, despite this occurring in up to 15% of injured patients. 6 In our study, there were three patients (mTBI #1, #5 and #7) whose saccadic reaction time rate did not resolve at the follow-up assessment.…”
Section: Discussionmentioning
confidence: 99%